Analisis Perbandingan Dalam Menilai Tingkat Kesehatan Bank Dengan Menggunakan Metode CAMELS dan RGEC (Studi pada Bank Umum BUMN yang Terdaftar di BEI Periode 2017-2021) - Achmad Achmad; Ahmad Faizul Muttaqin Anwar Musthofa (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2023)
Banks as intermediary institutions have a very important role in driving the Indonesian economy, especially state-owned banks which are state-owned banks, so banks must be managed carefully and need special supervision from the government. This study was conducted with the aim of finding out how the soundness of state-owned banks is using the CAMELS and RGEC methods, as well as the point of difference between the two methods. The type of research used is comparative descriptive with a quantitative approach. The data source used is secondary data. The data collection method in this research is library research and documentation study in the form of an annual report which is downloaded through the official website of the IDX (www.idx.co.id) and the official website of the company that is the subject of the research. From the results of this study, it can be seen that the assessment of the soundness level of state-owned commercial banks using the CAMELS and RGEC methods has different results. The results of the recapitulation of the Health Level Assessment of BUMN Commercial Banks based on the CAMELS Method in the last 5 years show that the health conditions of Banks BRI, BNI and Bank Mandiri are in a "Very Healthy" condition. Meanwhile, Bank BTN is in a “Healthy” condition. Meanwhile, the results of the recapitulation of the Health Level Assessment of BUMN Commercial Banks based on the RGEC Method in the last 5 years show that the health conditions of Bank BRI and Bank Mandiri are in a "Very Healthy" condition. Meanwhile, Bank BNI and BTN are in a "healthy" condition. The difference in the assessment results from the two methods is because the CAMELS method is more focused on the upside side of the business, while the RGEC method is not only focused on the upside side of the business, but also covers the downside side of the business. So that the RGEC method is considered a more comprehensive bank soundness assessment solution.